Relation of Lipid and High Sensitivity C-Reactive Protein Levels to Severity of Coronary Artery Stenosis - FUJITA, Isao; TAKEMOTO, Syunji; HIROTA, Shigeru; TAKAHASHI, Masahiko; KUROKI, Keiichirou; HORI, Keisuke; KAJIKAWA, Yutaka; INOUE, Masafumi; FUCHIMOTO, Yasuko (Japanese Journal of National Medical Services, 2006)
We designed the present study to evaluate the association of various lipid components and high sensitivity C-reactive protein (hs-CRP) with coronary artery stenosis. Levels of triglyceride (TG), remnant-like particle cholesterol (RLP-C), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein (LDL-C), lipoprotein-(a) [LP(a)], uric acid, fasting blood glucose, and hs-CRP were measured in 115 patients who underwent diagnostic coronary angiograms. LDL-C, TC/HDL-C ratio, LDL-C/HDL ratio and uric acid showed significant differences between patients with and without coronary artery stenosis. And we evaluated in a blinded manner according to three scores: vessel score (0-3 points for 0-3 vessels with coronary artery disease), stenosis score (0-3 points based on the number and severity of coronary stenosis or lesions: 0 for none, 1 for coronary lesion with diameter stenosis less than 50%, 2 for 50%-75%, and 3 for more than 75% diameter stenosis), and extent score (0-3 points based on segment-extension-of all coronary lesions within the total coronary vessel length). Multivariate regression analysis revealed that LDL-C levels show a linear correlation with the extent and severity of CAD on angiography. However, hs-CRP did not show a significant difference. Our current retrospective study disclosed that LDL-C, LDL/HDL ratio, TC/HDL ratio and uric acid are closely associated with coronary stenosis.